2023
DOI: 10.1108/k-04-2022-0553
|View full text |Cite
|
Sign up to set email alerts
|

The influence of collaborative innovation network characteristics on firm innovation performance from the perspective of innovation ecosystem

Abstract: PurposeThis study is aimed at making an inspection of the effects of collaborative innovation network characteristics on firm innovation performance, and the intermediary roles of knowledge transfer efficiency is taken into account.Design/methodology/approachThis study used a convenient sampling method to obtain population and samples. Using data obtained by publishing online and paper questionnaires, and using on-site interviews in Anhui Province in the Yangtze River Delta region of China, descriptive analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…In terms of the innovation performance, Wang et al found that network centrality and relationship strength have a promotion effect on knowledge dissemination efficiency and enterprise innovation performance [13]. According to Li and Liu , structural embeddedness has a favorable effect on the enterprise innovation effect in environmental protection, and the diversity of partners has a corrective effect on the relationship between the two mentioned above [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of the innovation performance, Wang et al found that network centrality and relationship strength have a promotion effect on knowledge dissemination efficiency and enterprise innovation performance [13]. According to Li and Liu , structural embeddedness has a favorable effect on the enterprise innovation effect in environmental protection, and the diversity of partners has a corrective effect on the relationship between the two mentioned above [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Others highlight the role of innovation as a crucial determinant of business performance and employee performance in an organisation [ 66 , 67 ]. These results are also related to the organisations' strategies, technological capabilities, and processes that workers adopt when developing innovation [ 68 ]. For this reason, it is crucial to study the effects of this use of technologies to evaluate their performance and innovation capacity in the organisation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The correlation coefficient can be called transfer coefficient, expressed as a j (0 < a j < 1). If Member 2 chooses knowledge transfer action, the direct benefit of Member 1 can be expressed as U 1 1 ¼ a 1 k 2 . Hypothesis 3: Knowledge has aggregation effects.…”
Section: Plos Onementioning
confidence: 99%
“…Perceived benefits matrix. (1) When the strategies of game players (members 1 and 2) are knowledge transfer and knowledge transfer, according to Hypothesis 2-6, it can be deduced that the direct benefit of Member 1 is…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation